Questions of assessment of biological assets in financial accounting - Ravshanov Alisher Boba kulovich, (THE INNOVATION ECONOMY, 2026)
In the practice of financial accounting, “biological assets” are recognized as an important object of finan cial accounting and reporting. Correct organization of accounting of biological assets further improves the quality indicators of financial reporting. The article presents the author’s analysis of the current state of accounting of bio logical assets based on national standards and problems of accounting of biological assets based on international standards, as well as ways to solve them